Gemini 1.5 Retrieval Accuracy Degradation for Fine-Grained Visual Details Beyond 500K Tokens - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 14 peer-reviewed papers addressing the following research question: How does the retrieval accuracy of fine-grained visual details degrade in Gemini 1.5 models as the number of interleaved image-text tokens exceeds 500k. 11 claims were extracted from source literature; 11 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 8.7/10. This report is a machine-generated literature synthesis a
Machine-generated literature synthesis.